Measuring and characterising the functional business financial literacy of entrepreneurs: a framework and survey instrument - Valle, Tarryn (Department of Finance and Tax, 2022)
The successful establishment and survival of entrepreneurial businesses is critical to economic growth and employment creation. However, entrepreneurs require sufficient levels of business specific financial competency to operate viable and sustainable businesses. Without the ability to measure functional business financial literacy, it is challenging to provide the necessary training and support to entrepreneurs. Unfortunately, research within financial literacy focuses almost exclusively on the measurement and understanding of personal financial literacy, which centres on individuals' personal financial wellbeing. Personal financial literacy is not equivalent to the financial skills required to ensure business financial wellbeing. This study combines the practical application of business financial concepts with established financial literacy and education theory to better understand and measure entrepreneurs' functional business financial literacy levels. Specifically, this study comprises three components. The first component proposes a business specific financial competency framework for entrepreneurs. The objective of the conceptual financial competency framework is to establish what competencies entrepreneurs of different business sizes should achieve. The framework draws structure from the accounting cycle and overlays educational taxonomies to suggest an appropriate level of skills that entrepreneurs in businesses of different sizes require. The conceptual financial competencies framework is grounded in work conducted by the OECD/INFE and adopts the three dimensions of financial literacy formulated by the OECD, namely knowledge, behaviour and attitude. In the second component of the study, the financial competencies framework is used to develop a survey instrument. This research aims to focus the instrument creation on microbusiness entrepreneurs to address their business financial knowledge and their behaviour and attitudes. Rigour in the formulation of the instrument is ensured through an expert group's input, the undertaking of a pilot survey, and the use and analysis of empirical data from its administration to a convenience sample cohort of 123 South African entrepreneurs, including sole traders, microbusinesses, and small businesses, to quantitatively assess the instruments' reliability and validity. The third component is an exploratory application of the instrument that uses various demographic information about the respondents and their businesses with the objective of better understanding the factors that affect functional business financial literacy levels. Within the exploratory cohort, higher functional business financial literacy levels are found for entrepreneurs in larger-sized businesses than entrepreneurs in smaller businesses and entrepreneurs with higher education levels than those with less. However, once adjusting for other demographic factors, using a regression model with dummy variables and univariate and multivariate analysis, no gender difference in financial literacy levels is observable. Also, no correlation is apparent between the respondent's age or racial group, or the businesses age or type and the entrepreneurs' financial literacy levels. Although not based on a representative sample of the South African business environment, these findings provide an initial indication that entrepreneurial support programmes should be tailored based on the educational attainment level of the entrepreneur and dependent on the size of the entrepreneurial business. The study's main contributions are in conceptualising a framework for assessing the business financial literacy of entrepreneurs, including self-employed individuals, designing a flexible instrument for this purpose, and demonstrating the instrument's application in an initial exploratory assessment. As the application of the instrument, which focuses on the correlation of selected demographic factors with business financial literacy, is based on a convenience sample, the study's contribution is not primarily of an empirical nature. Instead, it provides a foundation for further planned empirical studies and related questions based on larger and more representative samples. While the instrument itself and the convenience sample were centred around the skills proposed for microbusiness entrepreneurs, the framework and instrument developed in this study are flexible and can be customised to accommodate a range of business and entrepreneur types. Therefore, the instrument is suitable as a starting point for more extensive surveys to inform actions and policies to improve functional business financial literacy, hence ultimately reducing business failure and supporting economic growth and job creation.